2022
DOI: 10.2138/am-2022-8006
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved Raman and luminescence spectroscopy of synthetic REE-doped hydroxylapatites and natural apatites

Abstract: Using continuous and time-resolved spectroscopy, we investigate Raman and luminescence signals from synthetic hydroxylapatites doped with trivalent REE including Dy 3+ , Eu 3+ , Nd 3+ , and Sm 3+ , as well as REE in natural apatites, with laser excitations at 532 nm and 785 nm. We demonstrate that time-resolved spectroscopy is an extremely efficient method to tone down the luminescence from Raman spectra or, alternatively, to investigate the luminescence signal without the interference from the Raman contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Phosphates such as apatite and merrillite have characteristic yet distinct Raman spectra. Their Raman spectra have been described in terrestrial and extraterrestrial samples 27,61–64 . The symmetric stretching vibration mode of PO 4 3− provides the most intense Raman peak between 950 and 990 cm −1 , labeled as ν 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Phosphates such as apatite and merrillite have characteristic yet distinct Raman spectra. Their Raman spectra have been described in terrestrial and extraterrestrial samples 27,61–64 . The symmetric stretching vibration mode of PO 4 3− provides the most intense Raman peak between 950 and 990 cm −1 , labeled as ν 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The total intensities of the luminescence peaks can then be represented against the gate delay, see Figure S5B. The lifetime is then calculated as the slope at origin of the regression line going through the experimental points, giving a value of 0.56 ms. Fau et al 27 revealed a linear correlation between lifetime and Eu concentration inside synthetic Eu‐doped apatites. Here we obtain a lower value compared to the lifetime in apatite.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations